Factors That Affect Longevity Of Business Relationships - Margaretha P. Berlianto; Innocentius Bernarto (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Globalization has brought changes to all aspects of economic life, socio-cultural, and human lifestyle. Globalization results in many emerging multinational corporations, varieties of food and restaurants from other countries that exist in Indonesia. The Serba Food Restaurant is the object of this study, in which it is a new comer in the restaurant business that is widely-known in the Jabodetabek area. This study intends to examine whether there is any effect of service quality on customer satisfaction, trust, interpersonal connectedness, and longevity of business relationships. A statistical test was conducted on the 103 respondents from the university students who have once eaten in the Serba Food Restaurant. This study uses the PLS-SEM method as a statistical tool. This study has found that service quality has a positive influence on customer satisfaction, customer satisfaction has a positive influence on trust, trust has a positive influence on customer satisfaction, customer satisfaction has a positive impact to longevity of business relationships, and trust has a positive influence on longevity of business relationships. However, service quality has no positive influence on trust, and interpersonal relationships have no positive influence on trust.This study has provided a valuable contribution to the Serba Food Restaurant in order to create its longevity of business relationships.